Pengaruh Kualitas Pelaporan Keuangan dan Jatuh Tempo Utang Terhadap Efisiensi Investasi Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2020-2023 - Zukhra Hayani; Said Mahdani (Universitas Teuku Umar, 2025)
The purpose of this study is to examine the effects of financial reporting quality and debt maturity on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange. The sample consisted of manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023, comprising 50 companies and 200 firm-year observations. The sample was selected using a purposive sampling method, and the data were analyzed using SPSS version 26. The results indicate that: (1) financial reporting quality has a significant effect on investment efficiency; (2) debt maturity has a significant effect on investment efficiency; and (3) financial reporting quality and debt maturity simultaneously have a significant effect on investment efficiency.